Sistem Pakar Diagnosa Penyakit Pada Tanaman Kedelai Hijau Menggunakan Metode Teorema Bayes - Rosid, Danu Fajar Nur; Purnomo, A.Sidiq (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
The periodic handling of soybean plant diseases is often overlooked, leading to frequentcrop failures. These crop failures cause panic among farmers who are unsure of what to dowithout an expert's guidance. Therefore, in this research, the author has developed an expertsystem using the Bayesian method to detect diseases in soybean plants. This system canprovide temporary solutions or handling methods to anticipate crop failures before seekingdirect assistance from an expert. The expert system is created as a web-based system withan accuracy rate of 86%.